2007
DOI: 10.1111/j.1468-1331.2007.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion in the elderly with nocturnal blood pressure fall

Abstract: Cerebrovascular disease may be linked with vascular autoregulation in aging. The aim of this study was to examine relation between nocturnal blood pressure (BP) fall and cerebral blood flow (CBF) changes in elderly men. The prospective 'Men born in 1914' cohort study has been in progress since 1968 and included 809 subjects. After 14 years from the last follow up, 97 subjects reached the age of 82 and underwent CBF measurement and 24 h ambulatory blood pressure monitoring. Diastolic BP at night decreased in 84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…14 Finally, in a small number of octogenarians, stroke incidence was not different according to the dipping pattern. 17 We observed that reverse dipping was strongly associated with future cardiovascular events in univariable Cox regression analysis, but this relationship was no longer significant after full adjustment. Age, male sex, and 24-hour BP were the stronger predictors in the multivariable models.…”
Section: Fagard and Cort Orthostatic Hypotension Versus Reverse Dippingmentioning
confidence: 91%
See 1 more Smart Citation
“…14 Finally, in a small number of octogenarians, stroke incidence was not different according to the dipping pattern. 17 We observed that reverse dipping was strongly associated with future cardiovascular events in univariable Cox regression analysis, but this relationship was no longer significant after full adjustment. Age, male sex, and 24-hour BP were the stronger predictors in the multivariable models.…”
Section: Fagard and Cort Orthostatic Hypotension Versus Reverse Dippingmentioning
confidence: 91%
“…[13][14][15][16][17][18][19] Daytime ABP is usually higher than nighttime ABP, and the reverse diurnal pattern is independently associated with a higher incidence of cardiovascular events 16,18,19 and mortality 13,15,16,18,19 in most but not all studies. 14,17 Also, OH carries a worse prognosis for all-cause 4,9,11,12 and cardiovascular mortality, 5,9 coronary heart disease (CHD), 7,8,11,12 stroke, 6 or an aggregate of cardiovascular events, 12 although not all of the studies agree with regard to mortality [1][2][3]10 or stroke. 11,12 OH has been defined as a reduction of systolic BP of Ն20 mm Hg or of diastolic BP of Ն10 mm Hg within 3 minutes of standing, 20 but this definition has been applied differently in the various prognostic studies.…”
mentioning
confidence: 99%
“…27,31,[33][34][35] Extreme dipping is a complex phenomenon. Contrary to the established notion that subjects with low nocturnal BP are at low cardiovascular risk, extreme dippers have a higher prevalence of silent cerebral infarction, deep white matter lesions and silent myocardial ischemia during sleep than dippers.…”
Section: Nocturnal Blood Pressure and Cardiovascular Risk Y Yano And mentioning
confidence: 99%
“…Contrary to the established notion that subjects with low nocturnal BP are at low cardiovascular risk, extreme dippers have a higher prevalence of silent cerebral infarction, deep white matter lesions and silent myocardial ischemia during sleep than dippers. 27,33,34,36,37 Nocturnal hypoperfusion at the brain and/or heart during extreme dipping may occur, leading to organ damage. This is particularly of concern in older hypertensive patients with impaired cerebral autoregulation.…”
Section: Nocturnal Blood Pressure and Cardiovascular Risk Y Yano And mentioning
confidence: 99%
“…Recent studies have emphasised the importance of physiological variations in BP in the prediction of cerebral blood flow (CBF) and cerebrovascular disease, particularly with reference to nocturnal BP fall 13 14. The integrity of cerebral vasoreactivity and autoregulation is crucial in maintaining a constant CBF in the face of such BP fluctuations.…”
mentioning
confidence: 99%